The Innovation of Market Structure and Sharia Governance Model of Islamic Financial Institutions - Fradini Brillyandra; Muflihul Fadhil; Mukhlis Mukhlis; Nanda Suryadi; Astri Ayu Purwati (Yayasan Pendidikan Islam Al-Matani, 2024)
Market structure significantly affects price manipulation and economic efficiency. From an Islamic perspective, market structures should allow freedom but remain bound by rules that uphold responsibility and justice. Among the four primary market forms—perfect competition, monopoly, oligopoly, and monopolistic competition—the perfect competition market is deemed most ideal as it fosters balanced and efficient economic activity, aligning with Islamic principles of fairness. Sharia governance is crucial for ensuring that Islamic financial institutions (IFIs) adhere to Islamic laws, avoiding prohibited practices like riba and maintaining the halal nature of profits. This research, using descriptive analysis, examines the market structure in Islam and the Sharia governance model of Islamic Financial Institutions (LKS) within Indonesia's legal framework. The study, through literature reviews and legal document analysis, finds that Indonesian regulations comprehensively address Sharia governance, outlining aspects such as regulation, organizational structure, processes, and functions, thereby ensuring adherence to Sharia principles and promoting ethical financial practices.